(untitled) (Fountain Journal of Natural and Applied Sciences, 2022)
Dysmenorrhea is a major gynaecological issue among female students in Nigeria. This study investigated the Prevalence, lifestyle factors, and health effects of dysmenorrhea among female students at private Universities in Osun State, Nigeria. The cross-sectional descriptive study used a multistage sampling procedure to select participants randomly across selected private Universities in Osun State. A validated-structured questionnaire was used to gather data from participants. Data analysis using descriptive and inferential statistics at p<0.05 was done with IBM SPSS Software version 27.0. A total of 365 female students participated in the study, with a mean age of 20.2 ± 1.88 years. The prevalence of dysmenorrhea was 68.8%, out of which 49.4% of the respondents reported they experienced moderate pain and 31.9% reported they experienced severe pain. Up to 58.4% of the participants engaged in some form of exercise, and 61.4% of the respondents have good dietary patterns, whereas close to half (46.8%) of the respondents were sometimes absent from work or school due to pain. There was a significant association between good dietary pattern and dysmenorrhea [X= 18.241; p-value= 0.008]. This study has shown that dysmenorrhea is a public health challenge among the female population. Therefore, a holistic health education intervention must be carried out among female University students on basic coping strategies to minimize menstrual pains. Keywords: Dysmenorrhea, Female Students, Lifestyle, Menstrual Pain, Prevalence